Under the sign of consumption: status, needs and styles - Toaldo, Mariângela Machado (2008)
Often, we seek to justify consumerist practices around discovering people's needs and finding objects to satisfy them. This view assumes that human needs are so objective that it is possible to identify their causes and their solutions. Not that this is impossible, but this movement does not happen that simple. The whole abstraction that surrounds the feelings, tastes, and stimuli that underlie the system of people's needs and satisfactions is discarded.